THE USE OF SOUND BOOK TO ENHANCE STUDENTS' ARABIC VOCABULARY MASTERY - Mardhatillah Mardhatillah; Ali Muhtadi (Jurnal Eduscience, 2025)
Purpose – The limited use of learning media by teachers, which leads to a primarily one-way learning process, is the main reason for this study. Student learning outcomes are adversely affected by this lack of interaction in the classroom, particularly in Arabic language studies. The study intends to (1) figure out whether students who are taught using the sound book 'أول كتاب and those who do not have a notable difference in their mastery of Arabic vocabulary and (2) assess how well the sound book 'أول كتاب enhance students' Arabic vocabulary mastery.